EDUCATIONAL AND CREATIVE ACTIVITY SENIOR STUDENTS AS A CONDITION FOR THE FORMATION OF THEIR MENTAL CULTURE - R.O. Pylnik (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the problem of forming of mental culture of senior pupils. The author proves to efficiency of the use of creative tasks for organization educational & creative activity, that is assists in the rise of motivation of studies and development of reflection position.